A retrospective analysis of electric burn patients admitted in King Fahad Central Hospital, Jizan, Saudi Arabia. Issue 2 (April 2019) - Najmi, Yahya; Kumar, Pramod
Highlights: The incidence of electric burn in Saudi Arabia is increasing. Information on demographic profile and health facility for electric burn in Jizan, Saudi Arabia. The data will be useful in public health policy formulation and prevention strategy. Abstract: Background: Electrical burns incidence is increasing due to increased industrialization and increased use of electricity and electric domestic appliances. High morbidity and mortality associated with increasing incidence of electric injury may consume alarming high amount of resources and healthcare budget. Objective: Present study of epidemiological variables of electrical injuries may help to take preventive measures, improve services and plan resource allocation. Methods: Fifty seven records of all admitted electrical burn patients in KFCH, Jizan burn unit from January 2011 to December 2017 was reviewed and data about personal details, cause of burn, percentage of burn, ECG changes, isolated microorganism, treatment given, complication and final outcome were analyzed using descriptive statistics. Results: Electric burn constituted 93 (9.48%) of all burns unit admission. Overall average age was 28.67 ± 14.43 year; Male to female ratio was 10.4:1; High voltage to low voltage injury was 4.38:1; Contact to flash burn ratio was 2:1; Commonest region involves was upper limb 88.24%; and 29.26% cases had associated injuries. Significant ECG changes were noticed in 25% patients and culture was positive for bacterial growth in 76.19% (32/42) cases including ESBL in 7.14%, MRSA in 7.14% and CRE in 2.38% cases. A total of 73.078% cases underwent surgery with an average of 2.63 surgeries per patients; and 26.92% cases underwent major/minor amputations. Conclusion: Electric burn causes significant morbidity and mortality and can be prevented easily. It was emphasized that most of the electrical injuries can be prevented by education, policy implementation and use of safety PPE. Also, early surgical intervention was viewed as major required change to improve outcome.